Bimbingan dan konseling Layanan Bimbingan Kelompok Dengan Penggunaan Permainan "I've Got You" Di SMA Negeri 1 Kurun, Kuala Kurun - Oktamia Karuniaty Sangalang; mimi suriatie; nopi feronika; sunaryo . (JURNAL PENDIDIKAN, 2021)
The role and contribution of teachers is highly expected in the interest of the effectiveness and efficiency of Guidance and Counseling services in schools. Teachers can also act as counselors for their students. The purpose of this service is "to know the participation of teachers in implementing group guidance services with[1] the "I've Got You" game method at Senior High School of Sekolah Menengah Atas Negeri-1 (SMAN-1) Kurun, Kuala Kurun, Kuala Kurun Regency, Central Kalimantan Province". The sample is 41 teachers at SMAN-1 Kurun. The data was collected using a check list, in the form of a list of questions given to the teachers of SMAN-1 Kurun. How to analyze data to test the reality of teacher participation in schools on the implementation of group guidance services, devotees use percentage calculations. The results of the service show that almost all components of the goals in service are carried out with a high percentage of 100% by teachers in schools. This means that teachers really participate and support the Group Guidance Service at SMAN-1 Kurun